Dampak ESG (Environmental, Social, And Governance) terhadap Kinerja Perusahaan: Studi Kasus PT Pertamina dan PT Shell - Muhammad Faqih Rosadi; Syakila Wanda Wisafasha; Tiara Nurfadhilah (Letterlijk, 2025)
This article analyzes the impact of the implementation of Environmental, Social, and Governance (ESG) principles on the performance of energy companies, with case studies on PT Pertamina and PT Shell. This research aims to understand how ESG aspects affect corporate image, business continuity, and financial and non-financial performance. The method used is a literature study with a descriptive qualitative approach, reviewing annual reports, ESG ratings, as well as scientific journal publications and news. The results show that companies with a high commitment to ESG tend to have a better reputation, attract more investors, and are able to reduce long-term operational risks. This research is expected to provide policy recommendations for energy companies in Indonesia in responding to global sustainability challenges.